Model Diversi terhadap Anak Pelaku Tindak Pidana Pencurian dengan Pemberatan dalam Sistem Peradilan Pidana Anak untuk Mewujudkan Kepastian Hukum - James Tanardi Febrianto; Ismail; Dewi Iryani (Jurnal Hukum Lex Generalis, 2025)
This research examines the tension between legal ideality and the empirical reality of implementing Restorative Justice for children who commit theft under aggravating circumstances (pencurian dengan pemberatan). Normatively, Law Number 11 of 2012 concerning the Juvenile Criminal Justice System (SPPA Law) and its derivative regulations establish Restorative Justice-based diversion as the primary approach to protect the best interests of the child and avoid stigmatization. In practice, however, the application of diversion for aggravated theft (Article 363 of the old Criminal Code or Article 477 of the new Criminal Code) is constrained by the "under seven years" imprisonment threat requirement stipulated in Article 7 paragraph (2) of the SPPA Law, despite the nature of the act often being similar to ordinary theft. This condition is exacerbated by regulatory disharmony and differing interpretations among law enforcement officers, leading to legal uncertainty and disparities in case handling. This research employs a normative legal method enriched by an empirical approach, analyzing primary legal materials (SPPA Law, Criminal Code and police, prosecutorial and Supreme Court regulations regarding Restorative Justice) and secondary legal materials (journals, scientific works and court decisions such as Bontang District Court Number 50/Pid.B/2009/PN.Btg and Semarang District Court Number 33/Pid.SusAnak/2018/PN.Smg), analyzed qualitatively. The findings demonstrate that: (1) the implementation of Restorative Justice/diversion for children in aggravated theft cases remains limited by the criminal threat provision, resulting in many children being formally processed through to sentencing despite the SPPA Law's philosophical priority on non-judicial settlement; and (2) an ideal holistic diversion model is required through the reformulation of Article 7 paragraph (2) of the SPPA Law—changing the phrase "under 7 years" to "maximum 7 years"—alongside the implementation of a graded diversion model based on objective parameters such as the value of loss and level of aggravation, as well as regulatory synchronization and inter-agency coordination through integrated technical guidelines and a unified database system.